Transitional occupations of southeastern Somerset Island, Nunavut - Damkjar, Eric (Études/Inuit/Studies, 2003)
AbstractFour transitional period sites on Somerset Island compare closely with High Arctic sites attributed to Independence II. The four sites are situated at elevations between Pre-Dorset and Early Dorset occupations in the same area. The sites are described, with an emphasis on architectural characteristics. Vertical slab midpassage structures are present at all sites along with artifact assemblages containing shallowly side-notched bifaces, "cloven hoof" lance heads, a closed socket harpoon head, burin-like tools, narrow microblades, and needles with gouged eyes. Some sites also have exterior hearths and possible caches. Radiocarbon dates place the occupations within the transitional period (i.e. 800-500 B.C.). As during Independence II, the sites are of various size (three small ones and a large one), and are in association with polynyas.